2009
DOI: 10.1007/s00418-009-0573-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression and localization of growth hormone receptor in the oviduct of cyclic and pregnant pigs and mid-implantation conceptuses

Abstract: Previously it was shown that growth hormone (GH) and its receptor (GH-R) are involved in growth-promoting events during early embryonic development. However, it is still unknown if GH-induced GH-R signalling may support other functions within the oviduct. The purpose of our study was to analyse GH-R expression and localization in the porcine oviduct during different stages of the oestrus cycle and pregnancy (days 2-3 post inseminationem to days 65-71). As shown by reverse transcription polymerase chain reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Physiological levels of intratubular PRL and GH possibly derived from the circulation are presently unknown; however, follicular fluid containing both hormones flows into the oviduct following ovulation ( Lyons et al, 2006 ), permitting their local effects. The possibility for PRL and GH actions within the oviduct is also supported by evidence for the expression of the respective receptors in mammalian oviductal cells ( Shao et al, 2008 ; Steffl et al, 2009 ). It should be emphasized that concentrations of PRL and GH enhancing destructive changes of M-II chromosomes are 10 to 20 times higher than physiological ones.…”
Section: Discussionmentioning
confidence: 90%
“…Physiological levels of intratubular PRL and GH possibly derived from the circulation are presently unknown; however, follicular fluid containing both hormones flows into the oviduct following ovulation ( Lyons et al, 2006 ), permitting their local effects. The possibility for PRL and GH actions within the oviduct is also supported by evidence for the expression of the respective receptors in mammalian oviductal cells ( Shao et al, 2008 ; Steffl et al, 2009 ). It should be emphasized that concentrations of PRL and GH enhancing destructive changes of M-II chromosomes are 10 to 20 times higher than physiological ones.…”
Section: Discussionmentioning
confidence: 90%
“…The gene expression of GH is not confined to the pituitary gland, since its mRNA and the protein that is coded by it are produced in many extrapituitary sites, such as testes and ovaries [5,6]. Substantial studies have shown the presence of GH/GHRs in the ovaries of various organisms, including fish, chicken, rats, mice, horses, pigs, monkeys, and humans [7][8][9][10][11][12][13]. The occurrence of GHRs in ovaries indicates that these organs are a target site of GH action.…”
Section: Introductionmentioning
confidence: 99%